Implementation of Fatwa on Hajj Bailout Fund in Islamic Financial Institutions: A Systematic Literature Review Using PRISMA Approach - Handoko, Luqman Hakim (AL-FALAH : Journal of Islamic Economics, 2024)
Purpose: This study aimed to examine the implementation of fatwa no.29 regarding to hajj Bailout.Design/Method/Approach: The data retrieved used PoP software from Google Scholar on 1/26/2024. To determine the data, this study used the PRISMA framework approach. Then the final data will analyzed using a systematic literature review (SLR). The total documents are 78 documents, and the final document analyzed is 23 documents.Findings: The result showed that the first article appeared in 2011. Most of the research is in the form of article journals and thesis of undergraduate. The case study areas of existing research are quite diverse, which can be grouped into three categories, namely case studies on Islamic Banks, Islamic Rural Banks, and KPPS or BMT. This study found that only a third of the research comply with the Fatwa, while two third do not comply with the Fatwa. Interestingly, most of the main cause of the practice does not comply with Shariah is violating provision no. 4 which is in determining the fee or Ujrah. Hopefully, the Shariah Supervisory Board (SSB) will pay more attention to the practice of Islamic Financial Institutions (IFI) in the industrial world. For future research, perhaps researchers can study in more depth and examine the implementation of remaining fatwas.Originality/Values: This study concern on mapping the practice of implementation of fatwa no.29 in Islamic financial industries in Indonesia.